Islamic Higher Education Role on Teacher Competence and Students' Learning Difficulties in Islamic School - Fauzi, Muhamad; Nursalim, Nursalim; Fadilah, Arif; Gunawan, Agus (Yayasan Letiges Konsultan Sosial, 2023)
Education is an inseparable integration regarding level and resources in higher education. This study aims to analyse the role of Islamic higher education in improving teacher competence and student learning difficulties. This research uses a qualitative method with a literature study approach. Research shows that Islamic higher education’s role is to build education, especially human resources, by developing and improving teacher competence to help students with learning difficulties. Islamic higher education is more attention to problem-solving in madrasah through seminars, training, research and educational evaluation. Efforts to increase teacher competence in overcoming learning difficulties through independence and motivation by increasing skills and experience in solving problems in the learning process. The implications of Islamic higher education facilitated teachers to communicate with parents and students, take inventory of learning difficulties, participate in professional activities independently, and carry out gradual and continuous evaluations.